Decreased salivary α-amylase activity responding to citric acid stimulation in Myasthenia gravis with malnutrition - Huang, Ye; Wang, Wen-kai; Zheng, Xiao-mei; Yang, Long; Wang, Li-hui; Qiu, Xiang-hong; Chen, Long-hui; Li, Ru-liu; Lin, Chuan-quan (PLOS ONE, 2022)
Objectives Malnutrition, defined according to Nutritional risk screening (NRS 2002), is commonly observed in patients of Myasthenia gravis (MG), a neuromuscular disorder manifested by varied degrees of skeletal muscle weakness. Because biochemical composition of saliva changes in correspondence to alterations in nutritional status, we tested our hypothesis that a certain saliva component(s) might serve as a biomarker(s) for nutrition status of MG, particularly for those MG patients with high risk of malnutrition. Materials and methods 60 MG patients and 60 subjects belonging to the healthy control group (HCG) were enrolled in this case-control study. The salivary α-amylase (sAA) activity, salivary flow rate (SFR), pH, total protein density (TPD), and the concentrations of chloride and calcium ions in MG group with or without malnutrition were measured before and after citric acid stimulation. Thereafter, the relationship between sAA activity and BMI was determined in MG and HCG. Results Compared with HCG, more patients with malnutrition, increased TPD and chloride and calcium concentrations but decreased pH value and SFR both before and after acid stimulation, as well as reduced sAA activity, pH and TPD responses to acid stimulation. MG with malnutrition showed decreased sAA activity and TPD responding to acid stimulation compared with those without malnutrition. Compared with normal BMI, sAA activity response to acid stimulation was reduced in low BMI. There was a significant strong positive correlation between the ratio of sAA activity and BMI in MG. Conclusions Salivary biochemical characteristics are abnormally altered in MG with malnutrition. Altered sAA activity responding to acid stimulation was associated with malnutrition. Clinical relevance Decreased sAA activity responding to acid stimulation can reflect malnutrition state and may be one potential screening marker for MG patients with high risk of malnutrition.